Pengaruh Kecerdasan Interpersonal dan Tanggung Jawab terhadap Kepercayaan Diri Siswa Kelas V SD Negeri se-Kecamatan Maesan Kabupaten Bondowoso - Mohammad Ali Akbar (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
This study aims to determine the significance of the influence of interpersonal intelligence and responsibility partially or simultaneously on self-confidence. This research used a quantitative approach with the type of ex-post facto research. The population of this research is 629 students of the fifth-grade elementary schools in Maesan District with 245 students as research sample which determined by The Slovin Formula. Data collection techniques used a psychological scale was tested on 150 students. The analysis prerequisite test includes the normality test used the Kolmogorov-Smirnov method, linearity test, multicollinearity test, and heteroscedasticity test. Hypothesis test used multiple linear regression analysis technique. The results of the analysis show that 1) interpersonal intelligence partially had a significant effect on self-confidence with an effective contribution of 14.22%; 2) partial responsibility had a significant effect on self-confidence with an effective contribution of 25.98%; and 3) interpersonal intelligence and responsibility simultaneously had a significant effect on self-confidence with a simultaneous contribution of 40.2%.